SAT0312 MICRORNA-125B as a potential fibrotic and apoptotic regulator in systemic sclerosis. (15th June 2017) - Kozlova, A; Pachera, E; Renoux, F; Rudnik, M; Maurer, B; Jüngel, A; Distler, JH; Kania, G; Distler, O
Abstract : Background: MicroRNAs (miRs) are a class of small, noncoding RNAs that regulate many biological processes. Some microRNAs are involved in skin fibrosis. Objectives: To analyze the differential expression, regulation and the pathophysiological role of miR-125b in systemic sclerosis (SSc). Methods: For screening a low density array was run on pooled RNA from fibroblasts derived from 3 SSc patients vs. 3 healthy controls (HC). For further validation we performed qPCR on RNA derived from cultured fibroblasts, whole skin biopsies as well as on paraffin fixed dermis and epidermis. Next, fibroblasts were stimulated with pro-inflammatory and/or pro-fibrotic cytokines such as TGFβ, IL-1β, -4, -13, -17A, TNFα and PDGF. In order to identify downstream effects of miR-125b, knockdown with anti-miR-125b (or scrambled controls) in HC fibroblasts was performed. RNA was isolated from healthy fibroblasts (n=4) after knockdown and was proceeded to deep sequencing using Illumina HiSeq2000. Sequencing data were validated using qPCR on HC as well as SSc fibroblasts. Apoptosis was assessed by Caspase-Glo 3/7 assay and immunofluorescence of cleaved caspase 3 on cultured fibroblasts. Results: Screening identified miR-125b as one of the candidate miRs differentially expressed in SSc. MiR-125b was confirmed by qPCR in primary dermal fibroblasts (SSc =11, HC =8), where it was downregulated by 47% (median expression 53%, Q1, 3 33%, 70%; p<0.01). MiR-125b expression appeared to be independent from main cytokines operative in SSc. Additionally, the expression of miR-125b was assessed in skin biopsies of both SSc patients (n=4) and HC (n=5). In SSc, miR-125b was downregulated by 35% (median expression 65%, Q1, 3 61%, 78%; p<0.05). To localize its expression in the skin, we separately analyzed miR-125b expression in dermis and epidermis of paraffin fixed skin. In both cases, expression of miR-125b was downregulated. RNA sequencing identified >3500 differentially expressed genes with p<0.05. More than half of the differently expressed genes with at least 15% change were predicted targets of miR-125b by TargetScan and MiRWalk, indicating successful functional inhibition of miR-125b. Gene ontology revealed extracellular matrix organization and apoptosis regulation as the two main clusters of differentially expressed genes. Among them, BAK1, BMF and BBC3 are participants of the BCL2 apoptosis pathway and predicted targets of miR-125b. Consistent with the sequencing results, qPCR showed that knockdown of miR-125b upregulates these genes 24, 48 and 72 hours after transfection (p<0.05 for each). That was confirmed also on protein level by Western blot. Accordingly, miR-125b knockdown resulted in a higher rate of apoptosis (mean±SD: 60% ± 29%, p<0.01) compared to scrambled controls, measured by Caspase-Glo 3/7 assay. Moreover, miR-125b knockdown reduced TGFβ-induced αSMA expression both on RNA and protein levels, suggesting that miR-125b might play an additional role in the cytoskeletal reorganization of fibroblasts during fibrosis. Conclusions: MiR-125b is differentially expressed in SSc skin and primary dermal fibroblasts. MiR-125b downregulation increases apoptosis, inhibits cytoskeletal reorganization and therefore might become a potential anti-fibrotic therapeutic strategy. Disclosure of Interest: A. Kozlova: None declared, E. Pachera: None declared, F. Renoux Grant/research support from: Swisslife, M. Rudnik: None declared, B. Maurer Shareholder of: Patent licensed: mir-29 for the treatment of systemic sclerosis, Grant/research support from: AbbVie, Protagen, EMDO, Novartis, Pfizer, Roche, Actelion, A. Jüngel: None declared, J. Distler Shareholder of: 4D Science, Grant/research support from: Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi, UCB, G. Kania Grant/research support from: Bayer, O. Distler Shareholder of: Patent licensed: mir-29 for the treatment of systemic sclerosis, Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha